MANAJEMEN PENDIDIKAN AGAMA ISLAM DI PONDOK PESANTREN DARUL QUR'AN - Mulyadi Mulyadi (KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the management of Islamic religious education at Darul Qur'an Islamic Boarding School based on the management functions of planning, organizing, actuating, and controlling (POAC). The study employed a qualitative approach using a case study design. Data were collected through observations, in-depth interviews with the head of the boarding school, administrators, teachers, and students, as well as documentation of institutional records. Data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that the management of Islamic religious education has implemented the POAC functions in an integrated manner. Planning is carried out through the development of educational programs that integrate formal education, Islamic studies, and Qur'an memorization. Organizing is reflected in the clear distribution of responsibilities among school leaders, administrators, and teachers. The implementation of education emphasizes both religious knowledge and character development, while supervision is conducted through academic assessments, Qur'an memorization evaluations, and discipline monitoring. Supporting factors include strong leadership commitment and a well-established religious culture, whereas the main challenges involve limited human resources, curriculum integration, and the optimization of technology utilization. This study recommends strengthening teacher competencies, improving the integrated curriculum, and implementing technology-based educational management systems to enhance the quality of Islamic religious education in Islamic boarding schools.